Enkele prinsipiële fasette: die wiskunde en paradigmas in die ekonomiese wetenskap - Naudé, W. A. (Koers, 1993)
It is argued in this paper that the development of mathematics has had a profound effect upon the research paradigms of economics. Economists ’ early attempts to imitate the natural sciences have led them to an increasing quantification of their own science, with the consequence that recent developments in mathematics, such as the Theory of Chaos and the Theory of ('atastrophe, together with the implications from quantum physics, are causing a paradigm shift in economics. This paradigm shift has been turning away from a positivistic view of economic science towards a normative one a view where there seems to he greater acceptance of the principle that science cannot be free from value judgements. Tor the Christian economist these developments are to be welcomed. In the light of this, the paper concludes with a Scriptural perspective on the rote of mathematics in economics.